PARTICIPATION BASED MODEL OF SHIP CREW MANAGEMENT - Bielić, Toni; Ivanišević, Dalibor; Gundić, Ana (Promet - Traffic&Transportation, 2014)
<!–[if gte mso 9]> 800x600 <![endif]–> This paper analyse the participation - based model on board the ship as possibly optimal leadership model existing in the shipping industry with accent on decision - making process. In the paper authors have tried to define master’s behaviour model and management style identifying drawbacks and disadvantages of vertical, pyramidal organization with master on the top. Paper describes efficiency of decision making within team organization and optimization of a ship’s organisation by introducing teamwork on board the ship. Three examples of the ship’s accidents are studied and evaluated through “Leader - participation” model. The model of participation based management as a model of the teamwork has been applied in studying the cause - and - effect of accidents with the critical review of the communication and managing the human resources on a ship. The results have showed that the cause of all three accidents is the autocratic behaviour of the leaders and lack of communication within teams. <!–[if gte mso 9]> Normal 0 21 false false false HR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:’Table Normal’; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:’’; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:’Times New Roman’,’serif’; –> <!–[endif] –>